LEARNERS’ STRATEGIES TO DEVELOP THEIR COMMUNICATIVE COMPETENCE - Bhusal, Durga (International Journal of Language and Literary Studies, 2020)
Language Learning Strategies (LLSs) are specific actions, behaviors, steps, or techniques that the learners use them to improve their performance which is important for L2/FL learning and teaching. These strategies are as affecting factors on success or failure of the language learning process. Hence, this paper explores the English language learners’ learning strategies to develop their communicative competence within the theoretical stance of Oxford’s 1990 Language Learning Strategies (LLSs). The study is qualitative in nature where four participants were interviewed to understand their ontological perspectives and practices of different LLSs to enhance their communicative ability in English. The findings show the learners seemed to be usual strategy users. However, social, affective, and metacognitive strategies frequent strategies for developing their communicative competence. It further depicts learners are not always aware of the influence of consciously using language learning strategies for making their learning quicker and more effective. Thus, the teachers need to be the one who helps their students develop the awareness of language learning strategies and enable them to use a wider range of appropriate strategies for further success in their communicative competence.